Long-term results of intrastromal ring implantation for keratoconus - Henrique Celso Duarte de Rezende Rocha; Bernardo Kaplan Moscovici; Daniel Diniz da Gama; Renato Ambrósio Júnior; Marcos Pereira de Ávila (Revista Brasileira de Oftalmologia)
ABSTRACT Objective: To evaluate refractive and topographic outcomes before and at least 7 years after intrastromal ring segment implantation surgery in patients with keratoconus. Methods: Long-term retrospective longitudinal study carried out with 35 patients (62 eyes) aged 10 to 30 who underwent intrastromal ring segment implantation using a manual technique. Different arc rings were analyzed across various keratoconus types. Results: Significant improvements in topographic astigmatism (p = 0.001) and corrected distance visual acuity (p < 0.001) were observed, with no significant changes in keratometry (p = 0.099) and a slight decrease in pachymetry (p = 0.033). Statistically significant improvements in K1 were noted with two 160° arc rings. K2 showed improvements with all arc rings except for one 210° ring. Topographic astigmatism improved notably with two 160° arc rings. No significant changes occurred between six months after surgery and final visits. Conclusion: Long-term follow-up demonstrated favorable outcomes post-intrastromal ring segment implantation, particularly in manifest refraction and corrected distance visual acuity. Vision gain was common, though endothelial cell counts decreased, especially with two-ring segments. Thicker rings reduced astigmatism more significantly, whereas two-ring segments reduced keratometry. Notably, 210° arc rings did not reduce topographic astigmatism but did decrease refractive astigmatism.